Penerapan Model Teams Games Tournament (TGT) dengan Permainan Teka-Teki Silang (TTS) terhadap Keterampilan Berpikir Kritis Peserta Didik - Nurul Aisyah; Purwo Susongko; Mukhammad Aji Fatkhurrohman (Cakrawala: Jurnal Pendidikan, 2019)
This study aims to determine the improvement of students' critical thinking skills through the Teams Games Tournament (TGT) model with crossword puzzles (TTS). This research is an experimental study with the design of The One Group Pretest-Posttest. This research was conducted at SMP Negeri 4 Adiwerna 2018/2019 academic year involving 32 students in water pollution material. The instruments in the study used test and non-test instruments. The research test instruments were tested using validity test, reliability test, level of difficulty and distinguishing power. As well as non-test instruments, the study was tested by expert validators using the LKS validation sheet assessment. Data analysis techniques to test hypotheses are carried out using the "Paired Sample T Test" test. The results show that the TGT cooperative learning model with TTS can improve students' critical thinking skills.